The effect of the experimental chronic hyperglycemia on the kidney and myocardium - Yarmolenko, Olha; Bumeister, Valentyna; Polak, Stefan; Gordienko, Olena; Prykhodko, Olha; Demikhova, Nadiia; Shkatula, Yurii; Demikhov, Andrii (Ukrainian Journal of Nephrology and Dialysis, 2021)
Abstract. The number of patients with diabetes increases annually. Modern forecasts predict that diabetes will be the seventh leading cause of death in 2030. Despite many significant advances in the research of diabetes and the use of new modern treatments, the disease is still progressing, and it is necessary to continue to study the effects of diabetes on human systems and organs: kidney and myocardium. Methods. A total of 24 rats of reproductive age (6 months old) were involved in this experimental study. Experimental rats were injected with alloxan intraperitoneally once at a dose of 20 mg/100 g on an empty stomach. In addition, they received a 10% glucose solution 24 hours after alloxan injection and a 5% glucose solution during the experiment. We measured glucose level with Accu-Chek Advantage (Boehringer, Germany) after 2, 12, and 24 hours after alloxan injection, and then weekly. The subjects of the investigation were kidney and heart of the experimental (n=12) and control (n=12) animals for correct comparative analysis. Results. The average blood glucose level remained at 11 mmol/L ± 2 mmol/L. During the experimental period, the rats’ weight gain, dilation of both ventricles and relative renal weight gain were determined. By the histological examination of the myocardium, we revealed polymorphic nuclei, perinuclear cytolysis, fragmentation, wavy-like deformation of cardiomyocytes, stromal and perivascular edema, uneven filling of blood vessels, and local fibrosis. Thinning of fibrous capsule and cortical layer, destruction of nephrons, and hemorrhages were detected in the kidney. Conclusions. Our study confirms the robustness of alloxan-induced hyperglycemia in rats. We came to this conclusion because the early changes in the kidneys and heart are explained by the development of microangiopathies, which is a typical feature of the pathogenesis of diabetes. With prolonged exposure to chronic hyperglycemia, structural disorders of vital organs are worsened. This experimental model could be used for conducting comprehensive research aimed to study the mechanisms of diabetes mellitus, the effects of hyperglycemia on organs and tissues, and correct the complications.